Spatio-temporal patterns of foraging and feeding behavior of Elachistocleis bicolor (Anura: Microhylidae) - Lopez, Javier Alejandro (2017)
We analyzed spatio-temporal patterns and behavior of the foraging activity of the myrmecophagous frog Elachistocleis bicolor. We delimit ten 1m2 plots and recorded the number of frogs, distance between individuals and foraging behavior at half-hour intervals, during nine days. Using a generalized linear mixed model, we evaluated the maximum, minimum, and average daily temperature, microhabitat temperature, relative humidity, atmospheric pressure, the number of days since the last rain and last 48 hours accumulated rainfall as explanatory variables of frogs’ activity. The variables that best explained frogs’ activity were: mean atmospheric pressure, number of days since last rain and accumulated rainfall. Frogs showed an aggregated distribution pattern when foraging (Morisita standardized index= 0.501). The average distance between frogs was 47.53±25.28 mm. Frogs displayed a combined (active-passive) foraging strategy, actively searching ant trails, digging with their heads on trails running under the mulch, and them passively preying on ants as they pass through. Results showed that the E. bicolor foraging activity followed a circadian cycle that is regulated by several climatic variables, and that these frogs aggregated when foraging for ants.